(untitled) (European Journal of Marketing and Economics, 2020)
The relationship between organization and environment, based on the need to gather information and find resources, is increasingly characterized by a high level of uncertainty. Uncertainty means that managers do not have enough information and time to anticipate changes and make good decisions. More and more managers make decisions about new problems or situations. The level of risk increases, as well as the degree of complexity that the decision maker has to face. Under these conditions, organizations are moving towards the use of groups. The main purpose of the current research is to identify what are the most important benefits and limits of the group referring to its size, taking into analysis the banking institutions. For the current study is adopted the quantitative research and for the data collection is used the questionnaire. A total of 344 questionnaire are distributed. 80 percent of the participants agree that group size affects the quality of the decisions made and most of them prefer small groups. Also, most of them believe that within large groups are more conflicts, the relationships between members are more formal, the attention and individual commitment are lower than in small groups, the consensus is difficult, decisions can be made only through a voting process and there are no delays in decision-making, but coordination problems are not necessarily higher than within small groups.